Social Responsibility Disclosures: Links to Financial Violations and Performance - Africano, Fernando; Desiana, Lidia; Sakti, Ilham Prawidi (Journal of Accounting Science, 2025)
General Background: Corporate social responsibility (CSR) disclosure reflects a company’s accountability to societal and environmental concerns, making it essential to explore the factors influencing such disclosure. Specific Background: This study investigates CSR disclosure in the context of non-financial disclosures by companies listed on the Indonesia Stock Exchange (IDX), providing empirical evidence and theoretical insights. Knowledge Gap: While previous research has examined CSR disclosure, the interplay between financial pressure, firm size, financial performance, regulatory compliance, and environmental impacts remains underexplored. Aims and Methods: The study aims to analyze how these factors collectively influence CSR disclosure. Using secondary data from the Financial Services Authority and the IDX, a quantitative approach is applied with path analysis conducted via SPSS software. Results: Financial pressure significantly affects compliance with financial regulations. Firm size impacts environmental outcomes, which, in turn, along with firm size, drive CSR disclosure. Environmental impact mediates the relationship between firm size and CSR disclosure. Novelty: This study uniquely identifies the mediating roles of financial performance and environmental impact in the relationships among financial pressure, regulatory violations, firm size, and CSR disclosure. Implications: CSR embodies an organization's responsibility to address the societal and environmental effects of its activities, advocating ethical, transparent practices that foster sustainable development and community well-being.